Poly(ethylene chlorotrifluoroethylene) membrane formation via thermally induced phase separation (TIPS) - Roh, Il Juhn. (2013)
Poly(ethylene chlorotrifluoroethylene) (ECTFE) is a 1:1 alternating copolymer of ethylene and chlorotrifluoroethylene that offers excellent resistance in chemically and thermally challenging environments. ECTFE membranes with a variety of microstructures have been fabricated via thermally induced phase separation (TIPS) with dibutyl phthalate (DBP) as the diluent. A continuous flat sheet extrusion apparatus with a double rotating drum was used that permitted controlling both the casting solution thickness and axial tension on the nascent membrane. Initial compositions of ECTFE/DBP solutions in the liquid–liquid region of the binary phase diagram were chosen, resulting in membranes with an interconnected pore structure. The effects of several important process parameters were studied to determine their effect on the structure and properties of the membrane. The parameters evaluated included the initial ECTFE concentration, cooling rate, membrane thickness, co-extrusion of diluent, and stretching of the nascent membrane. The resulting membranes were characterized using SEM, porometry, and permeation measurements. For the range of process parameters studied, ECTFE membranes exhibited a decrease in surface porosity with increasing initial polymer concentration and cooling rate. The effect of membrane thickness on the permeation flux was not significant. Co-extrusion of diluent increased the surface porosity and eliminated the dense skin that was otherwise present under rapid cooling conditions. Subsequent stretching of the nascent membrane resulted in a more open structure and a significant increase in the permeation flux.